TESTING THE RELATIONSHIP BETWEEN PUBLIC EXPENDITURES AND TAX REVENUES BY FOURIER METHOD: THE CASE OF PALESTINE - Othman Sawafta; Aytül Bişgin (Ekonomi Maliye İşletme Dergisi, 2025)
Understanding the direction of the relationship between public expenditures and tax revenues is critical for achieving fiscal balances and formulating sustainable public policies. The study, which aims to analyze the long-run relationship between public expenditures and tax revenues in Palestine, covers the period 2011Q1-2024Q2 and consists of 54 quarterly observations. In the analysis of the study, the FKPSS unit root test and Fourier cointegration (FSHIN) analysis, which allow for slow and soft breaks and are more successful in capturing structural changes, are used as econometric methods. In addition, the causality relationship between the variables is determined by the Toda Yamamoto causality. According to the unit root test results of the variables, it is concluded that both public expenditures and tax revenues variables are non-stationary at the level. As a result of the FSHIN cointegration test, no long-run cointegration relationship was found between public expenditures and tax revenues. According to the Toda Yamamoto causality test, while there is no causality relationship from tax revenues to public expenditures at the 5% level of significance, there is a unidirectional causality relationship from public expenditures to tax revenues at the 5% level of significance. The results support the validity of the Expenditure-Tax Hypothesis and reveal that public expenditures increase tax revenues by stimulating economic activity. The study shows the fragility and external dependence of the fiscal structure in Palestine and provides policy recommendations for long-term fiscal sustainability.